Clinical Characteristics of Gastric Duplication in Children - Liu, Fei; Xu, Xiaogang; Lan, Menglong; Tao, Boyuan; Liang, Zijian; Zeng, Jixiao (Frontiers in Pediatrics, 2022)
Background: To investigate the clinical characteristics of gastric duplication (GD) in children. Methods: The clinical data of 17 children with gastric duplication who were treated in our hospital from July 2015 to June 2021 were analyzed retrospectively. There were 8 males and 9 females, aged from 2 months to 11 years. All children underwent laparoscopic gastric duplication resections and postoperative pathological diagnosis was gastric duplication. In addition, we searched and analyzed the literature on gastric duplication in children from January 1, 2011 to December 31, 2021 from the PubMed, EMBASE and Cochrane Library databases. Results: Gastric duplication was more common in females, with the most common cystic type occurring in the greater curvature of the stomach. Vomiting is the most common clinical manifestation. Ultrasound is an effective method for the early screening of GD. In this study, one patient who had multiple gastric duplications underwent laparoscopic cystectomy and mucosectomy, one patient was converted to open surgery, and all other children underwent laparoscopic cystectomies. The time to oral intake was 2.3 ± 1.0 days (range: 1~4 days), and the postoperative hospital stay was 5.7 ± 1.7 days (range: 2~9 days). All children were followed up for 6~77 months and had an uneventful recovery with the resolution of the preoperative symptoms. Conclusions: Gastric duplication in children lacks specific clinical manifestations, and the preoperative diagnosis rate is not high, so surgical exploration combined with pathological examination is often needed to make a clear diagnosis. Laparoscopic cystectomy can achieve good therapeutic results.